Northern Vietnamese Students’ Perceptions of Joint-training Programs - Đào, Tùng (VNU Journal of Science: Social Sciences and Humanities; Vol 31 No 4, 2015)
This research is conducted on 177 full-time students of joint-training programs offered in English in Vietnam. Five key factors have been recognized as important for a joint – training program in the field of economics - management, namely:  the participation of foreign lecturers;  learners must be regarded as "customers", and the training institutions in Vietnam must have appropriate customer care;  the foreign university that awards degrees must have high reputation, and high training quality;;  the foreign university that awards degrees must be widely known in Vietnam. Other factors as the teaching and assessment must be serious and hard enough;  the program must be taught entirely in a foreign language; 100% of textbooks and learning materials are in a foreign language and  there must have the participation of foreign students in the program in Vietnam; and the curriculum imported 100% from overseas  is less appealing to students. The research results also show that the assessment of participants has a high level of consensus and is not influenced by such personal factors as gender, study experience in joint-training programs and hometown background of learners. Keywords: In-country international join-training program;  attractiveness of the program; Vietnamese students.